Francine F. Rabinovitz y Felicity M. Trueblood, (comps.), Latin American Urban Research, v. 1. Beverly Hills, California, SAGE Publications, 1970, 438 p. - Necochea V., Andrés (Estudios Demográficos y Urbanos, 1973)
FRANCINE F. RABINOVITZ y FELICITY M. TRUEBLOOD, Comps., Latin American Urban Research, Vol. 1, Beverly Hills, California, SAGE Publications, 1970.